1980
DOI: 10.1288/00005537-198007000-00017
|View full text |Cite
|
Sign up to set email alerts
|

DNA and its synthesis in individual tumor cells from human upper respiratory tract squamous cell carcinomas

Abstract: Measurements of cytophotometric Feulgen DNA content and incorporation of 3H-thymidine were made in individual tumor cells from 58 patients with squamous cell carcinomas of the head-neck region. These measurements were correlated with a point ranking system for pathological grading for these types of tumors. Two of the parameters of the grading system, mode of invasion and nuclear polymorphism which had been found to be important factors in prognosis in clinical studies were correlated to the objective cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1984
1984
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…DNA measurements of squamous cell carcinomas of the head and neck region show similar DNA ploidy for tumours from various locations, and most tumours in the series reported by Holm et al, (1980) and Holm (1982) were DNA non-diploid. However, most tumours in the present series were DNA diploid (56%), possibly because small tumours tend to be DNA diploid (Kaplan et al, 1986;Tytor et al, 1987).…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…DNA measurements of squamous cell carcinomas of the head and neck region show similar DNA ploidy for tumours from various locations, and most tumours in the series reported by Holm et al, (1980) and Holm (1982) were DNA non-diploid. However, most tumours in the present series were DNA diploid (56%), possibly because small tumours tend to be DNA diploid (Kaplan et al, 1986;Tytor et al, 1987).…”
Section: Resultsmentioning
confidence: 65%
“…DNA content, proliferative activity (Sphase), and the occurrence of polyploid nuclei are more objective estimates and yield important complements to the clinical and pathological classification of many types of tumours (Atkin, 1976;Friedlander et al, 1984;Matsuura et al, 1986). Studies by Holm et al (1980) and Holm (1982) indicate that DNA measurements of oral cavity carcinomas may contain prognostic information.…”
mentioning
confidence: 99%
“…Extensive studies of other head and neck malignancies using flow cytometry have produced varied results [11, 12, 13, 14, 15]. Nonetheless, a strong correlation exists between nuclear DNA content and prognosis in upper respiratory tract carcinomas [16]. …”
Section: Discussionmentioning
confidence: 99%
“…These subjects must be questioned objectively. Ganzer et al [16] reported an average labeling index which varied from 4.1 to 14.6% from tumor to tumor specimen Holm et al [17] also felt that irregular thymidine incorporation was secondary to poor penetration during the 1-hour incubation and recommended suspension techniques.…”
Section: Methodological Reasonsmentioning
confidence: 99%